2017
DOI: 10.1007/s00784-017-2296-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the outcomes of direct pulp capping using Biodentine

Abstract: IntroductionThis study aimed to evaluate the prognostic value of factors with regard to the treatment outcome of direct pulp capping using Biodentine (Septodont, Saint-Maur-des-Fossés, France), in permanent teeth in which the pulps were exposed during caries removal.MethodsBetween 2010 and 2014, 112 teeth with deep carious lesions underwent direct pulp capping. The patients were followed up at 2–3 months and 1–1.5 years with a routine examination on both recall visits. Periapical radiographs were taken at 1–1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 48 publications
(64 reference statements)
3
80
0
13
Order By: Relevance
“…Other studies also support claims of Biodentine's and MTA's superiority over calcium hydroxide in terms of success rate in pulp capping procedures [107,108]. Another study reported that the success rate of DPC with BD is 90.9% in patients younger than 40 and 73.8% in patients 40 or older [109]. It is worth emphasizing that patient's age significantly influences the clinical outcome of this vital pulp therapy and needs to be taken into consideration when choosing successful treatment.…”
Section: Biodentinementioning
confidence: 59%
“…Other studies also support claims of Biodentine's and MTA's superiority over calcium hydroxide in terms of success rate in pulp capping procedures [107,108]. Another study reported that the success rate of DPC with BD is 90.9% in patients younger than 40 and 73.8% in patients 40 or older [109]. It is worth emphasizing that patient's age significantly influences the clinical outcome of this vital pulp therapy and needs to be taken into consideration when choosing successful treatment.…”
Section: Biodentinementioning
confidence: 59%
“…Biodentine TM (Septodont, Saint Maur des Fsses, France) is an example of a material based on hydrated calcium silicate. It shows odontotropic properties, that is, it stimulates the formation of reactive and reparative dentin and helps maintain proper sensitivity of the dental pulp [6][7][8][9]. The efficacy of the biological treatment of the pulp is higher in the younger patients as compared to the older patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…It shows odontotropic properties, that is, it stimulates the formation of reactive and reparative dentin and helps maintain proper sensitivity of the dental pulp [6][7][8][9]. The efficacy of the biological treatment of the pulp is higher in the younger patients as compared to the older patients [8]. This material is also used for sealing root perforation [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations